Assessing Dispositions Toward Ridicule and Laughter in the Workplace: Adapting and Validating the PhoPhiKat-9 Questionnaire - Hofmann, Jennifer; Ruch, Willibald; Proyer, René T.; Platt, Tracey; Gander, Fabian (Frontiers in Psychology, 2017)
The current paper addresses the measurement of three dispositions towards ridicule and laughter; i.e., gelotophobia (the fear of being laughed at), gelotophilia (the joy of being laughed at), and katagelasticism (the joy of laughing at others). These traits explain inter-individual differences in responses to humor, laughter, and social situations related to humorous encounters. First, an ultra-short form of the PhoPhiKat-45 (Ruch & Proyer, 2009) was adapted in two independent samples (Construction Sample N = 157; Replication Sample N = 1774). Second, we tested the validity of the PhoPhiKat-9 in two further independent samples. Results showed that the psychometric properties of the ultra-short form were acceptable and the proposed factor structure could be replicated. In Validation Sample 1 (N = 246), we investigated the relation of the three traits to responses in a ridicule and teasing scenario questionnaire. The results replicated findings from earlier studies by showing that gelotophobes assigned the same emotions to friendly teasing and malicious ridicule (predominantly low joy, high fear, and shame). Gelotophilia was mainly predicted by relating joy to both, teasing and ridicule scenarios, while katagelasticism was predicted by assigning joy and contempt to ridicule scenarios. In Validation Sample 2 (N = 1248), we investigated whether the fear of being laughed at is a vulnerability at the workplace: If friendly teasing and laughter of co-workers, superiors or customers are misperceived as being malicious, individuals may feel less satisfied and more stressed. The results from a representative sample of Swiss employees showed that individuals with a fear of being laughed at are generally less satisfied with life and work and experience more work stress. Moreover, gelotophilia went along with positive evaluations of one’s life and work, while katagelasticism was negatively related to work satisfaction and positively related to work stress. In order to establish good work practices and build procedures against workplace bullying, one needs to consider that individual differences impact on a person’s perception of being bullied and assessing the three dispositions may give important insights into team processes.